Influence of Quality Early Childhood Education Centres on Social Interaction of Pre-Primary School Pupils in Kwara State - Muraina Olanrewaju Kamilu; Ayoku Oba Baba; Habibat Bolanle Abdulkareem (MASI Mandiri Edukasi, 2022)
Poor-quality Early Childhood Education Centre (ECEC) can be detrimental to the development of children, as they may lead to poor social, emotional, educational, health, physical, and behavioral outcomes and the general well-being of children. However, this research examined the influence of quality ECEC centres on the social interaction of pre-primary school pupils in Kwara State. This study examines evidence on the influence of the quality of the ECE Centre on the Social interaction of pre-primary school pupils in Kwara State. The quantitative approach was adopted for the study while data was collected through a Questionnaire on the Quality of the ECE Centre and Observation rating scales on social interaction. Data collected were analyzed through descriptive statistics of frequency count and percentage scores. The results revealed that quality ECE Centre positively influenced social interaction between pre-primary school pupils and the overall development of children. At the same time, the study recommends that schools provide excess hands-on materials and allocate more play time and well enough space for play activities to foster children’s social interaction through quality ECE Centre, especially in Kwara State.